Far away and long ago: a South American odyssey - Edwards, Dianne (2010)
This lecture gives me a splendid opportunity to celebrate the importance of South America plants in palaeobotanical studies as they relate to a personal journey in the sub continent. This began in Venezuela many years ago when I began studies on a very diverse Middle to Upper Devonian flora, research now undertaken by Chris Berry. Its palaeogeographical significance remains intriguing, because, in similarities in assemblage composition, it relates to North America. In contrast subsequent studies in Argentina and Bolivia, earlier in the Devonian and Silurian, reveal a flora far more typical of Gondwana. Even more importantly it gives us some insight into high latitude vegetation, although sadly preservation is very poor in fragmentary fossils. Thus we have no comprehensive insights into early land plant ecosystems as, for example, is provided by the Rhynie Chert Lower Devonian hot spring deposit in Scotland. However a similar hot spring deposit recently discovered in the Jurassic of Santa Cruz Province, Argentina, provides a phenomenal window into an ecosystem preserved in situ and in great cellular detail, encompassing plants, animals and microbes. And so the odyssey ends in Patagonia on a high that would surely have been of major interest to naturalist W.H. Hudson (Far away and long ago: a history of my early life). It would not have been possible without the assistance and generosity of colleagues in La Plata, whose contributions will be further acknowledged in the lecture.